Andrzej Wajda’s Sweet Rush as an Extended Film Adaptation - Viren Denis G. (Художественная культура)
The film adaptation of Jarosław Iwaszkiewicz’s novel Sweet Rush (Tatarak) was the last in a series of films by Andrzej Wajda based on the prose of the outstanding Polish writer. The film was released in 2009 and was awarded the Alfred Bauer Prize at the Berlinale for ‘opening new perspectives on cinematic art’: indeed, not only did Wajda make a film that was uncharacteristic of his poetics, but he also expanded the potential of the cinematic language. Nevertheless, it received mixed reviews from critics and viewers. After Wajda’s death, it became obvious that this was one of the best, artistically bold works of the director’s later period, which, however, remained in the shadow of his more high-profile, journalistic works. Sweet Rush is a semi-documentary work about death and the experience of losing a loved one. Wajda constructs a three-level narrative, filming the original plot, showing the filming process and, finally, giving the floor to the leading actress Krystyna Janda: in monologues filmed in an empty room that gives a reference to the paintings of Edward Hopper, the actress talks about the death of her husband Edward Kłosiński, the famous cameraman and long-time collaborator of Wajda. Thus, fiction and reality, art and life are intertwined on the screen, and the literary source appears to be a catalyst for philosophical reflections on the fragility of existence.